Neuroprotective Effects against Glutamate-Induced HT-22 Hippocampal Cell Damage and Caenorhabditis elegans Lifespan/Healthspan Enhancing Activity of Auricularia polytricha Mushroom Extracts - Chanin Sillapachaiyaporn; Panthakarn Rangsinth; Sunita Nilkhet; Alison T. Ung; Siriporn Chuchawankul; Tewin Tencomnao (MDPI AG, 2021)
Oxidative stress is associated with several diseases, particularly neurodegenerative diseases, commonly found in the elderly. The attenuation of oxidative status is one of the alternatives for neuroprotection and anti-aging. Auricularia polytricha (AP), an edible mushroom, contains many therapeutic properties, including antioxidant properties. Herein, we report the effects of AP extracts on antioxidant, neuroprotective, and anti-aging activities. The neuroprotective effect of AP extracts against glutamate-induced HT-22 neuronal damage was determined by evaluating the cytotoxicity, intracellular reactive oxygen species (ROS) accumulation, and expression of antioxidant enzyme genes. Lifespan and healthspan assays were performed to examine the effects of AP extracts from Caenorhabditis elegans. We found that ethanolic extract (APE) attenuated glutamate-induced HT-22 cytotoxicity and increased the expression of antioxidant enzyme genes. Moreover, APE promoted in the longevity and health of the C. elegans. Chemical analysis of the extracts revealed that APE contains the highest quantity of flavonoids and a reasonable percentage of phenols. The lipophilic compounds in APE were identified by gas chromatography/mass spectrometry (GC/MS), revealing that APE mainly contains linoleic acid. Interestingly, linoleic acid suppressed neuronal toxicity and ROS accumulation from glutamate induction. These results indicate that AP could be an exciting natural source that may potentially serves as neuroprotective and anti-aging agents.